International comparisons of prices, output and productivity - Prasada Rao, D. S.; Salazar-Carrillo, Jorge (Contributions to economic analysis ;, 1996)
The present volume provides a collection of material on the subject of international comparisons, contributed by scholars from a range of relevant disciplines and geographical backgrounds. The papers in this volume have been classified into two broad groups united by overlapping themes. Part I includes essentially empirical papers intended to provide a clear picture of the different types of international comparisons that have been undertaken by various organizations and individuals. The papers relate to empirical studies of different sectoral and national income aggregates at both regional and global levels. The papers in Part II deal with methodological and analytical issues. Discussion of the appropriateness of various aggregation methods for international comparisons accounts for a major component of this section. The volume provides a set of studies on international comparisons of prices, output and productivity, and will provide a reference source for interested readers.